Sustainable development indicator systems: a study of the Swiss model - Santos, Márcia França Ribeiro Fernandes dos (Revista Gestão da Produção Operações e Sistemas, 2010)
This paper aims to present the structure of sustainable development indicators adopted by Swiss bodies that developed the Monitoring Sustainable Development (MONET) model whose publications are available on the Internet. In order to achieve this goal, a literature review is elaborated on the topic and then the ordering and conceptual milestones adopted in the Swiss proposal are shown. The study revealed that the country sought to promote integration between the three target dimensions of sustainable development: social solidarity, econo-mic efficiency and environmental responsibility.Keywords: Sustainability indicator; Sustainable development; Enviromental responsibility.